2022
DOI: 10.3390/su14095214
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Neural Network-Forecasted Compression Strength of Alkaline-Activated Slag Concretes

Abstract: The utilization of ordinary Portland cement (OPC) in conventional concretes is synonymous with high carbon emissions. To remedy this, an environmentally friendly concrete, alkaline-activated slag concrete (AASC), where OPC is completely replaced by ground granulated blast-furnace slag (GGBFS) industrial waste, is one of the currently pursued research interests. AASC is not commonly used in the construction industry due to limitations in experience and knowledge on the mix proportions and mechanical properties.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 76 publications
(80 reference statements)
0
10
0
Order By: Relevance
“…The amalgamation of powder content for each concrete has a different effect on power consumption. In most cases, the combination of cement and fly ash consumes more power during the mixing process, while the combination of cement and GGBS consumes the least power [21,26,47,48]. When observing these three grades of concrete, it can be seen that the combination of powder content is another factor that affects power consumption.…”
Section: Resultsmentioning
confidence: 99%
“…The amalgamation of powder content for each concrete has a different effect on power consumption. In most cases, the combination of cement and fly ash consumes more power during the mixing process, while the combination of cement and GGBS consumes the least power [21,26,47,48]. When observing these three grades of concrete, it can be seen that the combination of powder content is another factor that affects power consumption.…”
Section: Resultsmentioning
confidence: 99%
“…The μ value shown in the figure is based on exposure to photons at a 0.662 MeV energy level. Additives such as silica fume [ 130 ], GGBS [ 131 , 132 , 133 , 134 ], rice husk ash [ 135 , 136 ], palm oil fuel ash [ 137 , 138 , 139 , 140 , 141 ], and fly ash [ 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 ] serve as a partial cement replacement, which aims to reduce the carbon footprint of concrete [ 152 , 153 , 154 , 155 , 156 , 157 ]. The 60% increase in the fly ash replacement for cement in concrete reduced the μ value by 10% [ 63 ].…”
Section: Radiation Shieldingmentioning
confidence: 99%
“…The common observation in the results of these studies was that the copper slag addition increases the compressive strength over the control concrete. Most research has concluded that 30% to 40% of copper slag is the optimum replacement [38,79,80]. Some studies have confirmed that the compressive strength gradually increases up to 60%, and then decreases.…”
Section: Destructive Testing 431 Compressive Strengthmentioning
confidence: 99%
“…Some studies have confirmed that the compressive strength gradually increases up to 60%, and then decreases. Moreover, it was found that 100% copper slag replacement does not meet the mean target strength [38,81,82]. Adding fiber contributes to the enhancement of compressive strength by 6%.…”
Section: Destructive Testing 431 Compressive Strengthmentioning
confidence: 99%
See 1 more Smart Citation